A new mode of inner volcano growth: The “flower intrusive structure” - TIBALDI, ALESSANDRO; Pasquarè, F. (Earth and Planetary Science Letters, 2008)
A multiple-sill laccolith nested within a centrally-dipping sheet swarm is a recently discovered sub-volcanic structure, resembling a "flower" in section-view, which we have found in some eroded volcanoes in Iceland, suggesting that this structure can have some general relevance in deforming rock successions in volcanic areas. After a brief summary of the main characteristics of these examples, with details on Stardalur volcano, we present an evolutionary model to explain the whole structure. Both sills and sheets are fed by multiple pulses of magma following radial paths from a shallow chamber; the earlier vertical set of the radial sheets above the middle of the chamber are abruptly deflected into sills by the overlying lava succession. A proto-laccolith starts developing, composed of different, vertically stacked sills, originating from the central vertical feeder zone. Each sill contributes to the deformation of the overburden; room for intrusions is provided by the higher strain that can be attained by the widespread hyaloclastites and breccias which have a "softer" behaviour (with a lower Young's modulus) than the stiffer (higher Young's modulus) lava flows, combined with the doming of the overlying lavas. Later dikes get deflected outwards along the contact with the proto-laccolith and acquire a convex-upward shape, in cross-section. © 2008 Elsevier B.V. All rights reserved.